Young-onset amyotrophic lateral sclerosis: historical and other observations. - Turner, M; Barnwell, J; Al-Chalabi, A; Eisen, A (2012)
There is a wide range of age at initial symptom onset in amyotrophic lateral sclerosis despite a mean age of 65 years in population-based studies. 'Young-onset' amyotrophic lateral sclerosis typically refers to patients younger than ∼45 years and accounts for about 10% of cases in contemporary series. A review of published cases of amyotrophic lateral sclerosis from 1850 to 1950 revealed a far higher proportion of cases with young onset (>50%), with a steady decline to the contemporary figure. It is possible that this is not solely explained by increases in life expectancy. While there is still a rich variation in phenotypes among cases of young-onset amyotrophic lateral sclerosis, bulbar onset was found to be significantly under-represented in analysis of a large patient database, with implications for age-related vulnerabilities pertaining to focality of symptom onset. The timing of initiating pathological processes in relation to the emergence of symptoms is discussed, including the potential role of very early development and the interaction of epigenetic and environmental factors.